PENGARUH PEMBELAJARAN MATEMATIKA BERBASIS ETNOMATIKA TERHDAP HASIL BELAJAR SISWA - Dewi, Kartika; Aswita, Dian; Suryawati, Indah (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This research aims to determine whether the application of ethnomatics-based mathematics learning can influence the learning outcomes of class Vl students at SD Negeri 10 Banda Aceh. The research method used was experimental, with one group pre-test and post-test design. The population is all class VI students consisting of classes VI A and VI B, with the research sample being 24 class VI B students. Data was collected by administering tests and data analysis using Paired Sample t-test via SPSS 26. The research results showed that the Sig. (2 tailed) 0.000 0.05. So that H0 is rejected and Ha is accepted, it can be concluded that there is an influence from the application of ethnomatics-based mathematics learning on student learning outcomes at SD Negeri 10 Banda Aceh. The conclusion of this research is that ethnomatics-based mathematics learning encourages collaboration and high participation during the learning process